Evidence of Discrimination in Lending: An Extension - SHAFFER, SHERRILL (Journal of Finance, 1996)
ABSTRACT We generalize the model of Ferguson and Peters (1995) to allow for unequal recovery rates in the event of default by majority borrowers versus minority borrowers. This simple extension has two direct implications: (i) a uniform credit policy, as defined by Ferguson and Peters, entails cross‐subsidization across groups; and (ii) it is possible for a profit‐maximizing (and therefore economically nondiscriminatory) lending policy to generate lower average default rates among minority borrowers than among majority borrowers.